Undergraduate UK nutrition education might not adequately address weight management. Issue 2 (28th May 2015) - Rogerson, David; Soltani, Hora; Copeland, Robert
Abstract: Objective: Weight management appears to be multidimensional and complex, and registered nutritionists might work to educate, promote and provide weight-management services to communities, groups and individuals. However, nutrition education might not adequately reflect the weight-management requirements of individuals and groups. The aim of the present study was to investigate if the Association for Nutrition's undergraduate core competency framework for accredited Nutrition degrees sufficiently reflects the weight-management needs and experiences of individuals. Design: A qualitative investigation, conducted within critical realist ontology, was performed to understand the weight-management experiences of dieters and compare these with the Association for Nutrition's accreditation criteria for undergraduate Nutrition degrees. Setting: Framework analysis was used to identify and explain participants' experiences thematically and to compare these with the Association for Nutrition's core competency criteria. Subjects: Participants ( n 8) with weight-loss ( n 4) and weight-maintenance experiences ( n 4) were interviewed using semi-structured interviews to understand weight management at the agential level. Results: Participants described knowledge, exercise, planning, psychological constructs and behaviour-change techniques, determinants of eating and social support as features of weight management. The competency criteria provided clear guidance on all aspects discussed by the group, apart from psychological constructs and behaviour-change techniques and social support. Conclusions: Accredited Nutrition courses might not fully reflect the weight-management needs and experiences of individuals. Nutritionists might require greater knowledge of psychology and behaviour change to better understand and accommodate their clients' weight-management needs.